If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5v + 6 + -12V = -29 Reorder the terms: 6 + -12V + 5v = -29 Solving 6 + -12V + 5v = -29 Solving for variable 'V'. Move all terms containing V to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -12V + -6 + 5v = -29 + -6 Reorder the terms: 6 + -6 + -12V + 5v = -29 + -6 Combine like terms: 6 + -6 = 0 0 + -12V + 5v = -29 + -6 -12V + 5v = -29 + -6 Combine like terms: -29 + -6 = -35 -12V + 5v = -35 Add '-5v' to each side of the equation. -12V + 5v + -5v = -35 + -5v Combine like terms: 5v + -5v = 0 -12V + 0 = -35 + -5v -12V = -35 + -5v Divide each side by '-12'. V = 2.916666667 + 0.4166666667v Simplifying V = 2.916666667 + 0.4166666667v
| 49v^2-64= | | -n=-12 | | 21-4[14-(35-9)]=177 | | 21-4[14-(35-9)]=141 | | 121=9/5(x)+32 | | 3k^2-8k-8=0 | | -1-2=4-5x+6x | | 3k^2+8k+4=0 | | 3x-4[2x-(5x-9)]=141 | | (x^2)-10x+25=1 | | 3+y/3=4y+9-2 | | 3squared+5squared=csquared | | 19x=(9/2)-14 | | 5(a-8)+10=3(a-6) | | 1/3x+6=16 | | 2x^2+200x-2400=0 | | 2q/3-q/4=10 | | 60=1/2(8)(x+9) | | f(x)=8e^9x | | 5(p-2)=15 | | x^3-y^3=61x^2+y^2=41 | | 4(x+12)+7x=26 | | (1)/(x-4)+1=(14)/(x+2) | | 3(a-1)=a+1 | | 3a-9=a+1 | | (r-2)(r+5)=0 | | -(3+x)=2 | | (6+y)(4y+1)=0 | | (6+7)(4y+1)=0 | | 6b-10b=0 | | 4.5z-2.5z=2 | | 6(x-3)=48 |